Assessment of sVEGFR-1 concentration in patients with breast cancer - Thielemann, Anna; Kopczyński, Zygmunt; Baszczuk, Aleksandra; Ćwiklińska, Karolina; Grodecka-Gazdecka, Sylwia (Contemporary Oncology/Współczesna Onkologia, 2010)
Angiogenesis, the process in which new blood vessels arise from pre existing vessels, is necessary for the development and growth of solid cancer tumours and metastatic lesions. Vascular endothelial growth factor (VEGF) and the endothelial receptors VEGFR-1, VEGFR-2 and VEGFR-3 play an important role in this process. The aim of the study was to ascertain the value of assessment of sVEGFR-1 level in serum in women with primary breast cancer and its correlations with clinical status of the disease, histological malignancy, status of axillary lymph nodes and the size of the primary tumour. A group of 103 patients with primary breast cancer who had not undergone surgery was selected. Patients’ age ranged from 29 to 89 years old (mean 56 years ). All patients were treated in the Oncological Surgery Department of Poznan University of Medical Sciences. Forty healthy women aged from 24 to 75 (mean 47 years) formed a control group. The assessment of concentration of the soluble form of the vascular endothelial growth factor receptor sVEGFR-2 was performed in serum by an enzyme-linked immunosorbent assay (ELISA) (Quantikine test of R&D Systems, Abingdon, UK). The results of the study suggested that the level of VEGFR-1 in serum of women with breast cancer was significantly higher than in serum of healthy women. A relation was found between the level of sVEGFR-1 and the stage of clinical disease advancement. The statistical analysis showed a significant difference between sVEGFR-1 level in the control group compared to women with breast cancer in stages I, II and III of clinical disease advancement. There was a positive correlation between sVEGFR-1 level and aggressiveness of the disease. A similar correlation was not found between sVEGFR-1 level and the size of the primary tumour. Significant differences were also found between the group of women with metastases to the axillary lymph nodes and those with no metastases. The results of the study suggested that the concentration of the soluble form of the vascular endothelial growth factor sVEGFR-1 may represent a useful indicator for assessment of clinical disease advancement.